PENINGKATAN SKILL EDITING VIDEO KARANG TARUNA MENGGUNAKAN APLIKASI MOBILE PHONE CAPCUT DI DESA LENGKONG KULON - Dian Nurdiansyah; Putri Handayani; Fairuz Zabadi A (Universitas Pahlawan Tuanku Tambusai, 2023)
Village tourism potential is a resource or asset owned by a village and can be utilised as an attractive tourist attraction. Some aspects that usually become the potential of village tourism consist of: Aspects of nature, culture, history, and human resources that have an important role in how much success the programme will have. The utilisation of communication media technology in the millennial era has been used by the community, especially by people in the village, especially on social media such as Youtube, Instagram, TikTok. The research to be carried out will study the process of how the role of Karang Taruna Desa Lengkong Kulon utilises this media as part of promotion, one of which is through improving the audio-visual aspect using the CapCut application. CapCut is a video editing application available for iOS and Android devices. The method used in the research uses mixed methods with socialisation and training methods, so as to be able to play a key role in increasing the tourism potential in Lengkong Village, namely the tomb area of the national hero Raden Aria Wangsakara, where the figure has a very strong influence on the people of Banten, especially the Tangerang area. In addition to this tourism potential, socialisation and training can find the development of other tourism areas through promotional activities using audio visuals that are attractive and do not require relatively long time and space of professional editors in general.